Computational methods in engineering - Venkateshan, S. P.; Swaminathan, Prasanna (Academic Press, 2014)
Computational Methods in Engineering brings to light the numerous uses of numerical methods in engineering. It clearly explains the application of these methods mathematically and practically, emphasizing programming aspects when appropriate. By approaching the cross-disciplinary topic of numerical methods with a flexible approach, Computational Methods in Engineering encourages a well-rounded understanding of the subject. This book's teaching goes beyond the text-detailed exercises (with solutions), real examples of numerical methods in real engineering practices, flowcharts, and MATLAB codes all help you learn the methods directly in the medium that suits you best. Balanced discussion of mathematical principles and engineering applications. Detailed step-by-step exercises and practical engineering examples to help engineering students and other readers fully grasp the concepts. Concepts are explained through flowcharts and simple MATLAB codes to help you develop additional programming skills.